2015
DOI: 10.1364/boe.6.002609
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo multilaboratory investigation of the optical properties of the human head

Abstract: Abstract:The in-vivo optical properties of the human head are investigated in the 600-1100 nm range on different subjects using continuous wave and time domain diffuse optical spectroscopy. The work was performed in collaboration with different research groups and the different techniques were applied to the same subject. Data analysis was carried out using homogeneous and layered models and final results were also confirmed by Monte Carlo simulations. The depth sensitivity of each technique was investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 47 publications
(57 reference statements)
5
47
0
1
Order By: Relevance
“…Phantom measurements (source-detector separation = 2 cm, upper layer μ a = ~0.15 cm -1 and μ' s = ~15 cm -1 ) have demonstrated that a homogeneous fit retrieved the lower layer absorption within <15% discrepancy, as long as the thickness of the upper layer is ≤6 mm [43]. Also, comparing a two-layer model with a homogeneous model on the analysis of in vivo measurements on the forehead of 10 subjects, we obtained a good agreement in the estimate of μ a of the lower layer (~10 mm deep) between the homogeneous fit and the two-layer fit [44]. …”
Section: Resultsmentioning
confidence: 67%
“…Phantom measurements (source-detector separation = 2 cm, upper layer μ a = ~0.15 cm -1 and μ' s = ~15 cm -1 ) have demonstrated that a homogeneous fit retrieved the lower layer absorption within <15% discrepancy, as long as the thickness of the upper layer is ≤6 mm [43]. Also, comparing a two-layer model with a homogeneous model on the analysis of in vivo measurements on the forehead of 10 subjects, we obtained a good agreement in the estimate of μ a of the lower layer (~10 mm deep) between the homogeneous fit and the two-layer fit [44]. …”
Section: Resultsmentioning
confidence: 67%
“…It should be noted that a large variability in the baseline optical properties of human head tissues has been reported in the literature. 58 The regularization method employed here includes elements of the two most commonly used regularization methods used for ERPs, MEG, and EEG source analysis. The relative merits of minimum norm and LORETA as tools for conducting source analysis of electrophysiological data have been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The curve fitting procedure requires calculation of time-resolved data using a computational model of light propagation for given optical properties in an iterative manner, which as a consequence requires a fast and reliable model for a complex heterogeneous system [15,16].…”
Section: Introductionmentioning
confidence: 99%